Student Teachers' Instructional Performance of a College of Teacher Education - Romo, Necy Cesaria V.; Forneas, Sixto (JPAIR Multidisciplinary Research, 2010)
This study looked into the teaching performance of the Bachelor of Elementary Education (BEEd) student teachers of the College of Teacher Education, University of Northern Philippines, and School Year-2010. It looks into the level of teaching and academic performance of the student teachers. It also sought the level of academic performance and mastery of their subject matter and determined its significant relationship between the level of teaching performance and academic performance. The study used the descriptive survey method of research that analyzed the teaching performance pointed out by the student teachers. Mean, percentage and frequency counting, and the Pearson Product Moment coefficient of Correlation were used. Results showed that the student teachers' academic performance was very good. Most of them have a 94 percent mastery of the subject matter. Teacher's personality got the highest mean rating among the different criteria and Questioning Skills tend to be the lowest among them, but still fell on a very good descriptive rating.
Keywords: student teachers; teaching performance; academic performance